2017
DOI: 10.15171/jlms.2017.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Er:YAG Laser Irradiation and Different Concentrations of Sodium Hypochlorite on Shear Bond Strength of Composite to Primary Teeth’s Dentin

Abstract: Please cite this article as follows: Bahrololoomi Z, Dadkhah A, Alemrajabi M. The effect of Er:YAG laser irradiation and different concentrations of sodium hypochlorite on shear bond strength of composite to primary teeth's dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Sixteen in vitro studies [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen in vitro studies [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Most authors used primary molars [ 12 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 ], but Monghini et al [ 17 ] evaluated canines, and Mohammadi et al [ 29 ] used anterior teeth. Sample size varied from 2 [ 25 ] to 20 [ 28 , 31 ] teeth per group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present study, the melting of the dentin was insignificant, however, we found a slight fusion of the ends of collagen fibers. That process caused a partial blockage of dentin canals that can disturb the adhesion of filling materials or interrupt the formation of new clinical attachment after the periodontal recession coverage [52,53]. In order to solve this problem as well as open dentinal tubules as well as to increase its adhesion, the application of sodium subchloride was recommended by many authors [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…That process caused a partial blockage of dentin canals that can disturb the adhesion of filling materials or interrupt the formation of new clinical attachment after the periodontal recession coverage [52,53]. In order to solve this problem as well as open dentinal tubules as well as to increase its adhesion, the application of sodium subchloride was recommended by many authors [53][54][55]. Furthermore, any residues left in the cavity will result in inefficient adhesion [29] of gingival tissue to the tooth's surface.…”
Section: Discussionmentioning
confidence: 99%